Emergence of Female Pembarong in Reyog Art: Gender Stereotypes and Cultural Tightness in The Javanese Perspective - Sari, Ulfi Andrian; Yasri, Hayyun Lathifaty; Nulinnaja, Ratna (Institut Seni Indonesia Denpasar, 2025)
The presence of female pembarong (performers) in Java is interesting as a form of defying gender stereotypes. The female performers portray those who try to fight stereotypes and gender norms in a patriarchal society. Based on this phenomenon, this study aims to 1) explain the stereotypical experience of reyog Ponorogo female performers from the perspective of Javanese culture, 2) explain the experience of cultural tenacity of reyog Ponorogo female performers from the perspective of Javanese culture. The research was conducted in two places in Ponorogo. Sawoo Village in Sawoo Subdistrict, Ponorogo Regency which is the location of the Sardulo Nareswari reyog community and Plunturan Village in Pulung Subdistrict, Ponorogo Regency which is the location of the Putri Onggopati reyog community. This research uses a qualitative method. Data collection techniques used included interviews with female performers, observation of videos of female performers' performances from YouTube, Facebook, and Instagram, interview transcripts, triangulation of sources, and data visualization. Furthermore, the data was analyzed using an interactive model: data collection, data condensation, data display, and conclusions drawing. The labeling of the research results shows that: 1) Stereotypical views towards female performers have begun to diminish. Society began to accept their existence in reyog performance art. 2) The loosening of cultural constraints within Javanese tradition, with positive conditions that do not put aside their role as women, wives, and homemakers. These conditions provide freedom and creative opportunities for female performers.